INNOVATION IN HIGHER PEDAGOGICAL EDUCATION: REALITY AND PROSPECTS - Oliiar, Mariia (Mountain School of Ukrainian Carpaty, 2021)
The article analyzes the strategic aspects of the development of higher pedagogical education in Ukraine under modern conditions. It is determined that the process of progressive social change in Ukraine involves the democratization of the education system, including higher pedagogical and innovative development. In the publications of Ukrainian and foreign scholars there are attempts to develop strategic directions for the implementation of ideas of democratization and innovation in higher education. Under these conditions, university education faces a number of challenges that require immediate response. Modern research shows that today the pressure of competition on universities is stronger than ever. It is argued that the reasons for this are the increase in the number of higher education institutions and the massification of higher vocational education among the European population, including Ukraine, the market of foreign higher education available to Ukrainian students and the demographic crisis. All these factors caused fierce competition between higher education institutions, the rapid development of advertising and PR technologies aimed at fighting for the applicant, intensifying the process of ranking universities. The emphasis is placed on key ideas that unite the modern university educational space. First, the main figure in the new environment is the student as a consumer of educational services, therefore, it is necessary to take into account the needs and interests of the student's youth. Secondly, we need to focus on the new model of the classical university. In particular, the most important trend in modern education is the combination of innovation and tradition, the development of theoretical foundations and the search for effective practices for the introduction of educational innovations. The third challenge is that fundamental questions about the content of learning and ways to transfer it are again exacerbated by the spread of new communication technologies and social networks. In these conditions, the progress of development of a particular university directly depends on the extent to which it is able to provide organizational and methodological support for virtual mobility programs and contribute to the formation of digital competence of students and teachers. The essence of the state innovation policy in the field of higher education is revealed, which should be based on a system of principles, which include: meeting personal needs in education and meeting public demands for educated individuals prepared for innovation; integration of science, education and production; optimization of mechanisms of state regulation of education and self-government on democratic principles; state policy of genesis of innovative processes in the field of education; application the paradigm of lifelong learning in practice.